Pesan Dakwah Syekh Muhammad Abdul Gaos dalam Khidmat Ilmiah Manaqib - Aqhsal Arighi, Raihan (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2014)
The purpose of this study was to identify the khidmat ilmiah process as a variety of variants of the da'wah method, to analyze the composition of the da'wah message from Syekh Muhammad Abdul Gaos in the khidmat ilmiah manaqib. This research is based on David K. Berlo's theory of SMCR communication model. The research method used is descriptive qualitative approach. Based on the results of the study, it shows the khidmat ilmiah process of manaqib which begins with three stages, namely pre-manaqib khidmat amaliyah and khidmat ilmiah of manaqib composition of Syekh Muhammad Abdul Gaos da'wah message is generally divided into three categories, namely containing aqidah messages, shari'ah messages and moral messages, with emphasis on the message, namely talqin dhikr.